(untitled) (Devenires, 2021)
The notion of rage in Peter Sloterdijk’s thought is discussed in connection with his 2006 essay Rage and Time. An attempt is made to contrast thymós –as a fundamental impulse of the pre-Homeric understanding of rage– with Sloterdijk’sneocynicism, and with his critique of modern elitist cynicism. In this way, Sloterdijk’s psychopolitical courage seems to recall above all the epic songs of ancient Germania. The last part of the article deals with the idea of creating world banks of rage, conjecturing that the rage that Sloterdijk tries to rescue is virtually a “time bomb” that cannot be kept in our hands, and at the same time cannot be allowed to drop, at the risk of provoking clusters of actions filled with resentment and structural hatred.